Safety and Decision Support in Oncology - Hammond, P.; Harris, A. L.; Das, S. K.; Wyatt, J. C. (Methods of Information in Medicine, 1994)
The management of patients with cancer involves the administration of complex treatment protocols with frequent monitoring of the effects of treatment on the malignant disease as well as on the general health of the patient. The number and wide variety of protocols used in treatment trials, and the amount of clinical data generated suggest the need for computer-based support. The toxicity of many of the treatments used and the severity of the disease itself underline the safety-critical nature of all decisions made by oncologists, the physicians and surgeons who treat cancer patients. This paper presents recent work on the analysis of safety issues arising from the design and implementation of a protoype decision-support system for oncologists. It illustrates the benefits of combining both informal and formal approaches to the analysis and representation of safety, firmly based on a thorough and detailed study of the domain in cooperation with oncologists, pharmacists and medical informaticians.
Keywords: Safety; Decision Support; Oncology; Logic